Kajian Perspektif Kontraktor Terhadap Pematuhan Peraturan Pengurusan Sisa Pembinaan - Samsol Bahri, Mohd Shahrel; Seow, Ta Wee; Shafii, Haryati; Omar, Roshartini (Research in Management of Technology and Business, 2022)
The construction industry is a growing sector that contributes to the generation of large amounts of construction waste. Construction waste management is less emphasized by some contractors in the aspect of compliance with the guidelines. This research was conducted to study the knowledge, non-compliance factors, and methods of improving contractors’ compliance with construction waste management regulations. The respondents involved in this study consisted of G7 contractors in Johor Bahru, Johor. A total of 217 questionnaires were distributed and 91 responses were received back with a percentage of 42 percent. The data collection used in this study is a quantitative method through the distribution of questionnaire’s form to obtain primary data, while secondary data are obtained from the reading of reference materials and literature review. The results of this study found that most contractors know the construction waste management regulation that is being enforced. In addition, the factor of non-compliance among contractors with construction waste management rules is due to high management costs and the limited availability of waste landfills. The results also showed that the majority of respondents agreed with the method to improve contractors' compliance with regulation was through rule enforcement, legislation, ethics, management, and evaluation. In conclusion, this study is expected to benefit the construction industry, especially for the contractors to create a more effective and efficient construction waste management based on the regulation that has been gazetted.